Earnings over the lifecycle: the Mincer earnings function and its applications - Solomon W. Polachek (Institute for the Study of Labor (IZA), 2007)
In 1958 Jacob Mincer pioneered an important approach to understand how earnings are distributed across the population. In the years since Mincer's seminal work, he as well as his students and colleagues extended the original human capital model, reaching important conclusions about a whole array of observations pertaining to human well-being. This line of research explained why education enhances earnings; why earnings rise at a diminishing rate throughout one's life; why earnings growth is smaller for those anticipating intermittent labor force participation; why males earn more than females; why whites earn more than blacks; why occupational distributions differ by gender; why geographic and job mobility predominate among the young; and why numerous other labor market phenomena occur. This paper surveys the answers to these and other questions based on research emanating from Mincer's original earnings function specification.
Keywords: J1; 330; Mincer; earnings; earnings function; gender; discrimination; Lohn; Lebenszyklus; Humankapital; Bildungsertrag; Theorie; Schätzung; Welt